The Role of Tissue Renin-Angiotensin-Aldosterone System in the Development of Endothelial Dysfunction and Arterial Stiffness - Aroor, Annayya R.; DeMarco, Vincent; Jia, Guanghong; Sun, Zhe; Nistala, Ravi; Meininger, Gerald A.; Sowers, James (Frontiers in Endocrinology, 2013)
Epidemiological studies support the notion that arterial stiffness is an independent predictor of adverse cardiovascular events contributing significantly to systolic hypertension, impaired ventricular-arterial coupling and diastolic dysfunction, impairment in myocardial oxygen supply and demand, and progression of kidney disease. Although arterial stiffness is associated with aging, it is accelerated in the presence of obesity and diabetes. The prevalence of arterial stiffness parallels the increase of obesity that is occurring in epidemic proportions and is partly driven by a sedentary life style and consumption of a high fructose, high salt and high fat western diet. Although the underlying mechanisms and mediators of arterial stiffness are not well understood, accumulating evidence supports the role of insulin resistance and endothelial dysfunction. The local tissue renin angiotensin aldosterone system (RAAS) in the vascular tissue and immune cells and perivascular adipose tissue is recognized as an important element involved in endothelial dysfunction which contributes significantly to arterial stiffness. Activation of vascular RAAS is seen in humans and animal models of obesity and diabetes, and associated with enhanced oxidative stress and inflammation in the vascular tissue. The cross talk between angiotensin and aldosterone underscores the importance of mineralocorticoid receptors in modulation of insulin resistance, decreased bioavailability of nitric oxide, endothelial dysfunction and arterial stiffness. In addition, both innate and adaptive immunity are involved in this local tissue activation of RAAS. In this review we will attempt to present a unifying mechanism of how environmental and immunological factors are involved in this local tissue RAAS activation, and the role of this process in the development of endothelial dysfunction and arterial stiffness and targeting tissue RAAS activation.